Preliminary optimization of process conditions for biohydrogen production from sago wastewater - Ulhiza, Tami Asti; Mohamad Puad, Noor Illi; Azmi, Azlin Suhaida (2017)
High organic content in the untreated sago wastewater (SWW) can cause severe environmental pollution. The starch content in SWW can be utilized as a potential substrate for biohydrogen production. SWW taken from Johor contains 23700 mg/L COD and 0.146 g/l glucose. After acid pretreatment process using 1.5% (v/v) H2SO4 at 121oC for 60 minutes, the glucose content increased to 9.36 g/l. Early stage of optimization was carried out using one-factor-at-a-time (OFAT) method. The variables involved in this experiment were temperature, inoculum size and yeast extract. Enterobacter aerogenes (E. aerogenes) was used as hydrogen producer. It was found that the highest concentration of hydrogen was obtained when the temperature, inoculum size and yeast extract were 30oC, 5% and 3 g/l, respectively.